Sediment response to stream restoration in an agricultural watershed - John W. Clune; Gregory B. Noe; Matthew Cashman; Jessica D. DeWitt; Joseph M. Bell; Mitchell R. Weaver; James E. Colgin; Thomas R. Doody; Eliza L. Gross; Victor S. Cortes (Ecological Engineering, 2026)

Advances in diagnostic and therapeutic applications of mismatch repair loss in cancer - JT DeWitt; D. Jimenez-Tovar; A. Mazumder; S. Haricharan (DNA Repair, 2025)

A simple framework for maximizing camera trap detections using experimental trials - Philip D. DeWitt; Amy G. Cocksedge (Environmental Monitoring and Assessment, 2023)
Camera trap data are biased when an animal passes through a camera’s field of view but is not recorded. Cameras that operate using passive infrared sensors rely on their ability to detect thermal energy from the surface of an object. Optimal camera deployment consequently depends on the relationship between a sensor array and an animal. Here, we describe a general, experimental approach to evaluate detection errors that arise from the interaction between cameras and animals. We adapted distance sampling models and estimated the combined effects of distance, camera model, lens height, and vertical angle on the probability of detecting three different body sizes representing mammals that inhabit temperate, boreal, and arctic ecosystems. Detection probabilities were best explained by a half-normal-logistic mixture and were influenced by all experimental covariates. Detection monotonically declined when proxies were ≥6 m from the camera; however, models show that body size and camera model mediated the effect of distance on detection. Although not a focus of our study, we found that unmodeled heterogeneity arising from solar position has the potential to bias inferences where animal movements vary over time. Understanding heterogeneous detection probabilities is valuable when designing and analyzing camera trap studies. We provide a general experimental and analytical framework that ecologists, citizen scientists, and others can use and adapt to optimize camera protocols for various wildlife species and communities. Applying our framework can help ecologists assess trade-offs that arise from interactions among distance, cameras, and body sizes before committing resources to field data collection.

Identification of a candidate gene for a QTL for spikelet number per spike on wheat chromosome arm 7AL by high-resolution genetic mapping - Saarah Kuzay; Yunfeng Xu; Junli Zhang; Andrew Katz; Stephen Pearce; Zhenqi Su; Max Fraser; James A. Anderson; Gina Brown-Guedira; Noah DeWitt; Amanda Peters Haugrud; Justin D. Faris; et al. (Theoretical and Applied Genetics, 2019)

Gambusia quadruncus (Cyprinodontiformes: Poeciliidae): a new species of mosquitofish from east‐central México - R. B. Langerhans; M. E. Gifford; O. Domínguez‐Domínguez; D. García‐Bedoya; T. J. DeWitt (Journal of Fish Biology, 2012)
Gambusia quadruncus n. sp., the llanos mosquitofish, is described from east‐central México. The region inhabited by the species represents a hotspot of diversity of Gambusia , and G. quadruncus sometimes coexists with at least three congeners. The species differs from its closest relative, Gambusia affinis , in several characteristics with plausible effects on reproductive isolation, e.g . body size, body and fin morphology, male genital morphology (distal tip of gonopodium) and female anal spot morphology (colouration near the urogenital sinus). Moreover, combined analysis of mitochondrial and nuclear gene sequence data ( c . 2158 total base pairs) indicates reciprocal monophyly of G. quadruncus and its sister species G. affinis , with levels of genetic divergence suggesting the two species diverged from one another over a million years ago. The origin of G. quadruncus may reflect a vicariant event associated with Pliocene orogenesis in the Tamaulipas Arch and a frontal section of the Sierra Madre Oriental (Lleran Mesas). Gambusia quadruncus inhabits a variety of freshwater habitats across several river drainages, with its range spanning at least 350 km from north to south, covering over 25 000 km 2 . A key to aid identification of the species is provided.

Spatio-temporal variability and predictability of summer monsoon onset over the Philippines - V. Moron; A. Lucero; F. Hilario; B. Lyon; A. W. Robertson; D. DeWitt (Climate Dynamics, 2009)

Geochemical ecosystem engineering by the mud shrimp Upogebia pugettensis (Crustacea: Thalassinidae) in Yaquina Bay, Oregon: Density‐dependent effects on organic matter remineralization and nutrient cycling - Anthony F. D'Andrea; Theodore H. DeWitt (Limnology and Oceanography, 2009)
We investigated the effect of the thalassinid mud shrimp Upogebia pugettensis on organic matter and nutrient cycling on Idaho Flat, an intertidal flat in the Yaquina River estuary, Oregon. Field studies were conducted to measure carbon and nitrogen remineralization rates and benthic fluxes relative to shrimp population density. Organic carbon remineralization rates estimated from incubations increased with burrow density. Similarly, benthic oxygen uptake increased linearly with burrow density. Shrimp bioirrigation enhanced carbon remineralization up to 2.9 times; its effects on nitrogen cycling were even more dramatic, enhancing ammonification rates up to 7 times, nitrification rates between 3 and 9 times, and estimated denitrification up to 4 times relative to portions of the tide flat lacking shrimp. Bioirrigation by shrimp also reduced pore‐water inventories of dissolved inorganic nitrogen (DIN), resulting in DIN fluxes that increased exponentially with burrow density up to 15‐fold relative to No‐shrimp plots. For both C and N fluxes, the strongest density‐dependent relationships occurred with burrow hole density rather than shrimp population density or biomass. Combined with population mapping of mud shrimp populations on Idaho Flat, we estimate that total areal C and DIN effluxes on the tide flat were enhanced 1.9 and 3.7 times, respectively, relative to areal fluxes expected if no shrimp were present. Mud shrimp thus perform as geochemical ecosystem engineers that strongly affect the flux and fate of C and N in Pacific estuaries.

Suppression of Endogenous Antioxidant Enzymes by 2,3,7,8-Tetrachlorodibenzo-p-dioxin–Induced Oxidative Stress in Chicken Liver During Development - J. Lim; J. C. DeWitt; R. A. Sanders; J. B. Watkins; D. S. Henshel (Archives of Environmental Contamination and Toxicology, 2007)

STOIC: a study of coupled model climatology and variability in tropical ocean regions - Davey M.; Huddleston M.; Sperber K.; Braconnot P.; Bryan F.; Chen D.; Colman R.; Cooper C.; Cubasch U.; Delecluse P.; DeWitt D.; Fairhead L.; et al. (Climate Dynamics, 2002)

ENSIP: the El Niño simulation intercomparison project - M. Latif; K. Sperber; J. Arblaster; P. Braconnot; D. Chen; A. Colman; U. Cubasch; C. Cooper; P. Delecluse; D. Dewitt; L. Fairhead; G. Flato; et al. (Climate Dynamics, 2001)

Pharmacological evaluation of 1-(carboxymethyl)-3,5-diphenyl-2-methylbenzene, a novel arylacetic acid with potential anti-inflammatory properties - S. J. Cutler; C. DeWitt Blanton Jr.; D. T. Akin; F. B. Steinberg; A. B. Moore; J. A. Lott; T. C. Price; S. W. May; S. H. Pollock (Inflammation Research, 1998)